2020
DOI: 10.1007/s10140-020-01837-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurological emergencies associated with COVID-19: stroke and beyond

Abstract: Novel coronavirus disease (COVID-19) was declared a global pandemic on March 1, 2020. Neurological manifestations are now being reported worldwide, including emergent presentation with acute neurological changes as well as a comorbidity in hospitalized patients. There is limited knowledge on the neurologic manifestations of COVID-19 at present, with a wide array of neurological complications reported, ranging from ischemic stroke to acute demyelination and encephalitis. We report five cases of COVID-19 present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 20 publications
0
22
0
3
Order By: Relevance
“…In a multinational study on hospitalized patients with SARS-CoV-2 infection, Shahjouei et al [ 18 ] demonstrated an overall stroke risk of 0.5% (pooled 0.9%) with ischemic heart disease (OR 2.5, p = 0.006) and mechanical ventilaton (OR 1.9, p = 0.03) as independent predictors. Although less common, a subset of neurologic complications has been thought to be due a cytokine storm and multisystem inflammation resulting in acute demyelination, vasculitis, necrotizing encephalopathy, and posterior reversible encephalopathy syndrome [ 19 ]. Tsivgoulis et al [ 20 ] undertook a review of neurological manifestations during the COVID-19 pandemic and found predominantly mild neurological manifestations in the majority of infected patients, while multiple comorbidites were present with severe neurological disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a multinational study on hospitalized patients with SARS-CoV-2 infection, Shahjouei et al [ 18 ] demonstrated an overall stroke risk of 0.5% (pooled 0.9%) with ischemic heart disease (OR 2.5, p = 0.006) and mechanical ventilaton (OR 1.9, p = 0.03) as independent predictors. Although less common, a subset of neurologic complications has been thought to be due a cytokine storm and multisystem inflammation resulting in acute demyelination, vasculitis, necrotizing encephalopathy, and posterior reversible encephalopathy syndrome [ 19 ]. Tsivgoulis et al [ 20 ] undertook a review of neurological manifestations during the COVID-19 pandemic and found predominantly mild neurological manifestations in the majority of infected patients, while multiple comorbidites were present with severe neurological disease.…”
Section: Discussionmentioning
confidence: 99%
“…Amidst the COVID-19 pandemic, multiple neurological manifestations are increasingly being reported, including, ischemic stroke, intracranial hemorrhage, diffuse leukoencephalopathy, acute demyelination, and transient cytotoxic edema [ 8 ]. A cross-sectional study conducted between March 23 and May 7, 2020 evaluated the neuroimaging findings in 73 patients with COVID-19 who had acute de novo neurological manifestations: 43 had abnormal MRI findings, including mainly cerebrovascular thrombotic events, in addition to restricted diffusion foci within the corpus callosum, which was consistent with CLOCC [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another case report, A 33-year-old male suffering from morbid obesity, diabetes mellitus, and hypoxemic showed a respiratory failure secondary to COVID-19 affection. MRI presented widespread foci of the demolition of the myelin with restricted diffusion, most located in the corpus callosum and the pericallosal white matter [ 41 ]. Furthermore, Karapanayiotides et al described a 57-year-old male affected by COVID-19 along with particular localization and a concentric demyelination pattern.…”
Section: Evidence Of Covid-19 Virus Involvement In Demyelinationmentioning
confidence: 99%